2022
DOI: 10.21608/ajnsa.2022.125836.1558
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Impact of Spirulina and Chlorella on some Hematological and Biochemical Aspects in Irradiated Rats

Abstract: Background: Patients undergoing radiotherapy may suffer from many harmful effects including gut microbiota injury, therefore, the use of exogenous probiotics is suggested to reduce these effects. Aim: The present study aimed to determine the possible protective effect of Spirulina platensis and Chlorella vulgaris against radiation-induced hematological and biochemical disturbances in male albino rats. Materials and Methods: Spirulina or chlorella was administered orally at a dose level of 300 mg/kg body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
3
0
0
Order By: Relevance
“…On the other hand, Khattab et al [30] didn't notice any significant differences in the levels of ALT and AST in blood serum of Barkhiya ewes that were treated with spirulina powder for 8 weeks. Our results also contradicted the study of Badawy et al [31], who observed a significant decrease in level of ALT enzyme without affecting the level of AST in animals treated with SP for a week. Also, Alghonaim et al [32] didn't find any significant effect of SP on liver enzymes on day 90 of the experiment.…”
Section: Alanine Aminotransferase (Alt)contrasting
confidence: 99%
“…On the other hand, Khattab et al [30] didn't notice any significant differences in the levels of ALT and AST in blood serum of Barkhiya ewes that were treated with spirulina powder for 8 weeks. Our results also contradicted the study of Badawy et al [31], who observed a significant decrease in level of ALT enzyme without affecting the level of AST in animals treated with SP for a week. Also, Alghonaim et al [32] didn't find any significant effect of SP on liver enzymes on day 90 of the experiment.…”
Section: Alanine Aminotransferase (Alt)contrasting
confidence: 99%
“…The histological investigations of C. vulgaris and/or Orange peels supplementation in irradiated rats showed amelioration in liver fibrosis progression in accordance with the finding obtained by Abdel-Aziz et al 88 It could be attributed to amelioration of oxidative stress status and targeting TGF-β1 signaling pathway. 89…”
Section: Histopathological Observationsupporting
confidence: 89%
“…A high dose of ionizing radiation caused a significant (p ≤ 0.05) rise in ALT, AST, Urea, and Creatinine (the increased percentages recorded were 43.1%, 35.4%, 156.6%, and 183%, respectively as compared with the control group), in agreement with the data obtained by Darwish et al 53 and Ahmad et al 54 This increase could be attributed to the interaction of cellular membranes with the free radicals produced by gamma rays directly or indirectly which cause change in tissue permeability and enhancement of enzyme movement from its subcellular production sites to the extracellular fluid and consequently to blood. 55 However supplementation with orange peels and C. vulgaris cause a remarkable improvement (the percentages recorded were −7.5%, −7.1%, 33.2%, and 18.6%, respectively as compared with the control group), as shown in Table 2; in accordance with the data obtained by Badawya et al 56,57 and Ahmed et al 58 This effect may be due to the high quantities of phenolic compounds and their antioxidant capacities. 59…”
Section: The Effects On Liver and Kidney Functionssupporting
confidence: 86%
See 1 more Smart Citation
“…This was agreed with (Abd el-Aziz et al, 2022) who reported that oral administration of Chlorella vulgaris and Spirulina platensis increased RBCs, Hb, hematocrit and platelet count. This may be attributed to spirulina playing an important role in the erythropoiesis process (Badawy et al, 2022) and on the same side, Chlorella vulgaris improved heamato-biochemical parameters (Sayed et al, 2021) and also may attribute to feed with protein can improve the number of RBCs. CV and SP are rich in proteins and other nutrients, similar to that reported by Siman Juntak et al (2022).…”
Section: Discussionmentioning
confidence: 97%